Evalu ation of potato hybrids according to tuber flesh darkening and other useful agronomic characters under the conditions of Kirov Province - N. F. Sintsova; I. V. Lyskova; E. I. Kratyuk; V. M. Arkhipov (Труды по прикладной ботанике, генетике и селекции, 2021)
Background. Resistance of raw and boiled tuber flesh to darkening when potato is processed into potato-based products or consumed directly is an important requirement for new potato cultivars. Identification of hybrids resistant to tuber flesh darkening would contribute immensely to future breeding work.Materials and methods. Parent forms and hybrid progeny of potato were tested for five years (2016–2020) in Kirov Province using the methods and technologies approved for potato breeding process. The progeny of 10 cultivars used as pollinators was analyzed.Results and conclusions. Cultivars with high levels of resistance to the darkening of raw tuber flesh were selected in the collection nursery. A total of 62 accessions (or 24%) out of 256 were identified for the absence of darkening or only small traces thereof (8 points) in raw tubers. Medium and strong darkening of the flesh (4–5 points) was recorded for 45 accessions. Analyzing the progeny of pollinator cultivars showed an increased occurrence of hybrids resistant to tuber flesh darkening in the progeny of cv. ‘Manifest’: 71% of the studied hybrids had non-darkening flesh (9 points). Manifestation of tuber flesh darkening was found to depend on weather conditions during the growing season: the higher was the air temperature, the weaker was the darkening of raw tuber flesh, but when the soil moisture during tuberization was high, tuber flesh became more darkened. A statistically significant relationship was observed between the darkening of boiled tubers and the content of crude protein (r = 0.74) and vitamin C (r = 0.79). Hybrid 179-10 was identified for high productivity (32.5 t/ha) and crude protein content (1.54%), while the highest resistance to the darkening of raw and boiled potato tubers was registered in hybrid 72-13.